Impact of Inadequate Number of Lymph Nodes Examined on Survival in Stage II Colon Cancer - Wu, Qi; Zhang, Zhiyuan; Chen, Yijiao; Chang, Jiang; Jiang, Yudong; Zhu, Dexiang; Wei, Ye (Frontiers in Oncology, 2021)
Background Inadequate number of lymph nodes examined was not uncommon. We aimed to assess the clinical role of inadequate number of lymph nodes examined in stage II colon cancer. Methods The cancer data used in our study were obtained from the SEER (Surveillance, Epidemiology and End Results) program. Using the chi-square test, all the variables obtained in our study were compared based on whether patients had enough (≥12) lymph nodes examined. Kaplan–Meier analysis was used for overall survival (OS) analysis, and log-rank test was applied to compare different N stages with the total number of lymph nodes examined. Multivariate analysis was carried out by creating a Cox proportional hazard model to assess the prognostic roles of different variables. Results In total, 80,296 stage II/III colon cancer patients were recruited for our study. N0 stage with <8 lymph nodes examined would present with a worse prognosis compared to N1 stage (5-year OS rates, 51.6% vs. 57.1%, p < 0.001). Multivariate analyses indicated that OS of N0 stage with <8 lymph nodes examined was similar to that of N1 stage after adjusting for other recognized prognostic factors [hazard ratios (HRs) = 1.051, 95% confidence intervals (CIs) = 1.014–1.090, p = 0.018]. Conclusions N0 stage with less than eight lymph nodes examined in stage II colon cancer presented with no better OS compared to that of N1 stage. Stage II colon cancer with less than eight lymph nodes examined needed to be given greater emphasis in clinical practice.